ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN PEMBIAYAAN PADA PERBANKAN SYARIAH INDONESIA PERIODE 2006.01-2011.12 - Aidida Adelia Purnama (Media Ekonomi, 2012)
This study aims to determine the factors that influence the development of IslamicBanking Financing in Indonesia, including Third Party Funds (TPF),NonPerforming Financing (NPF),the level of reward certificates of Bank Indonesia(SWBI) and Financing to Deposit Ratio (FDR).The data used in this study is asecondary data with the monthly period 2006:01-2011:12.The Analysis techniqueused is the Multiple Linear Regression Methods premises OLS (Ordinary LeastSquare).The result show that the Third Party Funds(TPF) has positive andsignificant impact of Islamic Banking Distribution Financing. While the NonPerforming Financing (NPF) and the level of rewards Certificates of Bank Indonesia give negative and no significant impact and Financing to Deposit Ratiogive positive and no significant impact of Islamic Banking Financing Distribution.Keywords:Islamic Banking Financing Distribution, Third Party Funds (TPS),Non PerformingFinancing (NPF),Certificates Wadiah of Bank Indonesia (SWBI and Financing toDeposit Ratio (FDR)